Cyprus : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report, 2000)
Cyprus is broadly compliant with International Organization of Securities Commission (IOSCO) core principles in a number of areas including enforcement, cooperation with domestic and foreign regulators, principles for issuers, principles for market intermediaries, and market regulation. The following statistical data are presented: composition of gross-fixed capital formation, tourist travels and receipts, wage and productivity indicators, price indices, implicit deflators, monetary survey, financial indicators, social insurance funds, direction of trade, invisible transaction, balance of payments, international reserves, imports by commodity, and so on.